2021
DOI: 10.3390/ijms22105369
|View full text |Cite
|
Sign up to set email alerts
|

Oxonium Ion Guided Analysis of Quantitative Proteomics Data Reveals Site-Specific O-Glycosylation of Anterior Gradient Protein 2 (AGR2)

Abstract: Developments in mass spectrometry (MS)-based analyses of glycoproteins have been important to study changes in glycosylation related to disease. Recently, the characteristic pattern of oxonium ions in glycopeptide fragmentation spectra had been used to assign different sets of glycopeptides. In particular, this was helpful to discriminate between O-GalNAc and O-GlcNAc. Here, we thought to investigate how such information can be used to examine quantitative proteomics data. For this purpose, we used tandem mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Using HCD fragmentation, we could identify several product ions consistent with the presence of glycosylated moieties, together with some y- and b -type peptide fragments supporting these reporter glycopeptides, even though with some ambiguity in terms of glycosites assignment (Figure 4 C). The presence of GalNAc, the first sugar residue in O -glycans, could be further confirmed by several HexNAc cross ring fragments ( m/z 126.055, 168.066, 186.076, and 204.087; Figures 4 C-D and Figures S6 -7 and 11) and, in some cases, high 144.066/138.055 oxonium ions ratios 53 , 54 . We also explored HexNAc-triggered CID fragmentations for further glycopeptide validation, including the characterization of extended glycan chains ( Figure S6 ).…”
Section: Methodsmentioning
confidence: 65%
“…Using HCD fragmentation, we could identify several product ions consistent with the presence of glycosylated moieties, together with some y- and b -type peptide fragments supporting these reporter glycopeptides, even though with some ambiguity in terms of glycosites assignment (Figure 4 C). The presence of GalNAc, the first sugar residue in O -glycans, could be further confirmed by several HexNAc cross ring fragments ( m/z 126.055, 168.066, 186.076, and 204.087; Figures 4 C-D and Figures S6 -7 and 11) and, in some cases, high 144.066/138.055 oxonium ions ratios 53 , 54 . We also explored HexNAc-triggered CID fragmentations for further glycopeptide validation, including the characterization of extended glycan chains ( Figure S6 ).…”
Section: Methodsmentioning
confidence: 65%
“…Originally, the type A structure was fully elucidated through NMR analysis, which showed that the HexNAc is a GlcNAc, and that the N -methylthreonine-phospho moiety is attached to the C3 position ( 19 ). It has recently been suggested that the ratio between the abundance of the HexNAc oxonium ions at m/z 138.055 and 144.065 in MS/MS spectra of O -glycosylated peptides can be used to discriminate between a GlcNAc and GalNAc ( 22 , 23 ). More specifically, a ratio >2 would be indicative of a GlcNAc, which is supported by the MS/MS spectra of type A-modified peptides presented in this article.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of the oxonium ions at m/z 138.055 and 144.066 is consistent with a GlcNAc. 24,25 Of note, a signal at m/z 126.055 was observed that corresponds to a GlcNAc oxonium ion, which is distinct from the 126C TMT reporter ion (m/z 126.128).…”
Section: Alterations Of the Type A Glycan In The Cd0241− Cd0244 Mutan...mentioning
confidence: 99%